School breakfast and young children's absenteeism: Does meal location matter?. (December 2022) - Gottfried, Michael A.; Kirksey, Jacob
Highlights: This article addresses whether kindergartners and first graders who received Breakfast in the Classroom have different attendance outcomes. The dataset used in this study is the ECLS-K:2011. It is comprised of student assessment data long with contextual information from parents, teachers, and school administrators. Children who receive Breakfast in the Classroom miss fewer days of school and are less likely to be chronically absent. Abstract: Of all years of elementary school, kindergartners and first graders are disproportionately absent. To address this, there is a growing effort among both research and policy communities to identify and develop which school resources might be leveraged to improve absenteeism. This study contributes in this domain, by examining whether serving school breakfast in the classroom (as opposed to elsewhere at school) might be linked to better attendance outcomes for students in both kindergarten and first grade. Using nationally representative data (Early Childhood Longitudinal Study – Kindergarten Class of 2010–11) and controlling for unobserved confounding individual-level factors, our study finds that when schools moved breakfast into the classroom (from the cafeteria, for instance), children had fewer days absent as well as a decrease in the likelihood of being chronically absent. The results were not differentiated by specific student or school characteristics, thereby suggesting a generalizability across all students in the sample. These findings should motivate a policy conversation around ways to best leverage and change existing school settings to reduce children's absenteeism.